Optimalisasi Pelayanan Pemenuhan Kebutuhan Air Bersih Masyarakat Wakorumba Utara, Kabupaten Buton Utara: Studi Kasus Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat Labora - Anisah, Anisah; Baskara, Surya; Adami, Aryani (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2023)
The need for clean water each year generally increases, while the availability of clean water is increasingly limited. At first, local people at North Wakorumba used dug wells, river water, and rainwater to meet their needs for clean water. Along with the development to drill wells and river water, the government provided clean water, although only in certain villages in the sub-district. This type of research is descriptive-quantitative, a study to determine the clean water needs of the people at North Wakorumba, North Buton Regency, and reviewing spring discharge. The primary data are from the people of the North Wakorumba District, North. The secondary data used in population and customer data at PAMSIMAS Labora. Service optimization occurs at the PAMSIMAS Labora discharge and the intake and reservoir basins. The population projection for the next 10 years is 5,199 people, with the community's need for clean water in the research area for the next 10 years in 2031, which is 14.389 liters/second. With a total water debit of 18 liters/second.